2013
DOI: 10.7314/apjcp.2013.14.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Breast Cancer Patients in Northwest Iran

Abstract: Background: Breast cancer is the most frequently occurring cancer among Iranian women; however limited studies have been conducted to address survival rates. Objective: The objective was to examine survival rates in Tabriz (Northwest of Iran) and comparing with those of data reported from other cities and countries. Methods: Survival rates were calculated for one, three, five, seven and ten years for 271 breast cancer patients referred to one university clinic during 1997-2008. Results: Survival analysis demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
9
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 9 publications
4
9
3
Order By: Relevance
“…21,22 In agreement with other regional and global studies, our results revealed that the histological type of cancer and metastases are associated with survival differernces. 19,8,23 In our study, the three-year survival rate for localized tumor was 96.1% and this figure is consistent with another Saudi study as the authors documented that the localized cancer had a clearly better prognosis (Five-year survival rate = 67.5%). 7 Breast cancer is commonly treated by various combinations of surgery, radiotherapy, chemotherapy, and hormone therapy.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…21,22 In agreement with other regional and global studies, our results revealed that the histological type of cancer and metastases are associated with survival differernces. 19,8,23 In our study, the three-year survival rate for localized tumor was 96.1% and this figure is consistent with another Saudi study as the authors documented that the localized cancer had a clearly better prognosis (Five-year survival rate = 67.5%). 7 Breast cancer is commonly treated by various combinations of surgery, radiotherapy, chemotherapy, and hormone therapy.…”
supporting
confidence: 81%
“…Similar findings to our results were reported by a cohort study conducted in Tabriz University hospital, Iran, between 1997 and 2008 and it was observed that the overall survival at one and three years was 96% and 86% respectively. 8 Also in Iran a recent meta-analysis and systemic review (included 24 studies, 22745 participants) was conducted to assess the survival rate of breast cancer and the findings revealed that the one, three, five, and ten-year survival rates were 0.956, 0.808, 0.695, 0.559 respectively. 7 In England, as an example of a well developed country, 96% of women survive breast cancer for at least one year, and this is predicted to fall to 87% surviving for five years or more, 78% of women are predicted to survive their disease for ten years or more, as calculated by agestandardized net survival for patients diagnosed with breast cancer during 2010-2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside Thailand, while our median survival rate is higher than the 5.7 years found by a study of breast cancer patients in Malaysia (Abdullah et al, 2013), our findings are lower than those reported in Iran. A study of breast cancer patients after receiving radiotherapy in Iran found that the survival rates at 1, 3 and 5 years were 96.0% , 86% and 81.0%, respectively (Ziaei et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Movahedi et al (2012) also calculated the 5-year survival rate to be 72% in BC patients during 2001 -2006 (27); differences in the time of these studies could explain this gap. (31). These disparities between the results can be justified by geographical variations in socioeconomic factors, quality of health services (27), and time differences between the studies.…”
Section: Discussionmentioning
confidence: 99%